ANALYSIS OF LIQUIDITY, SOLVENCY, PROFITABILITY, ACTIVITY, INVESTMENT RATIO IN ASSESSING FINANCIAL PERFORMANCE ON TELECOMMUNICATIONS COMPANIES REGISTERED ON THE IDX YEAR 2020 – 2022 - Simarmata, Desi Kartika; Nasution, Nina Andriany (Proceeding of The International Conference on Business and Economics, 2024)
The aim of this research is to analyze Liquidity, Solvency, Profitability, Activity, Investment Ratios in Assessing Financial Performance in Telecommunication Companies Listed on the IDX in 2020 - 2022. The method used in this research is a quantitative descriptive method, the data in this research uses data secondary. Based on the research results, it shows that the Liquidity Ratio of PT. Inti Bangun Sejahtera, Tbk in 2021 was measured based on the Current Ratio of 280.86% which was declared very good in assessing Financial Performance. PT Solvency Ratio. Inti Bangun Sejahtera, Tbk in 2021 was measured based on the Debt to Asset Ratio of 31.03% which was declared very good in assessing Financial Performance. Profitability Ratio PT. Solusi Tunas Pratama Tbk in 2022 based on a Net Profit Margin of 49.59% is declared very good in assessing Financial Performance. The Activity Ratio which is measured based on the Total Asset Turnover Ratio is stated to be not good in assessing Financial Performance. Investment Ratio PT. Bali Towerindo Sentra Tbk in 2022, which was measured based on a Dividend Yield of 18.43%, was declared very good in assessing the Financial Performance of telecommunications companies listed on the IDX in 2020 - 2022.